P01.122 Safety, immunogenicity and optimization of the IMA950 multipeptide vaccine combined with Poly-ICLC in newly diagnosed HLA-A2 malignant glioma patients. (19th September 2018) - Migliorini, D; Dutoit, V; Allard, M; Mohan, S; Lobrinus, A; Merkler, D; Vargas, M; Walker, P R; Patrikidou, A; Dietrich, P
Abstract: Background: The clinical development of immunotherapy is still limited for patients with malignant glioma. We report the results of a phase I/II study of the IMA950 multipeptide vaccine adjuvanted with the TLR3 agonist poly-ICLC in association with radiochemotherapy in newly diagnosed HLA-A2+ malignant glioma patients. Material and Methods: Patients with newly diagnosed GBM (n=16) and grade III astrocytoma (n=3) were treated concomitantly with radiochemotherapy with the IMA950 multipeptide vaccine and poly-ICLC. The first 6 patients received IMA950 i.d. and poly-ICLC i.m. Afterwards, the protocol was amended and patients received IMA950 and poly-ICLC mixed and injected s.c. (n=7) or i.m. (n=6). Primary endpoints were safety and immunogenicity. Secondary endpoints were OS, PFS at 6 and 9 months, as well as immunological characterization of peripheral CD4 and CD8 T cell responses. Results: The IMA950/poly-ICLC vaccine was safe and well tolerated. Four patients presented cerebral edema with rapid recovery with standard management. For the first 6 patients, vaccine-induced CD8 T cell responses were restricted to a single peptide and CD4 responses were not detectable. After optimization of the vaccine formulation, we observed multipeptide CD8 and sustained Th1 CD4 T cell responses. For the entire cohort (n=19), CD8 T cell responses to a single or multiple peptides were observed in 63.2% and 36.8% of patients, respectively. An encouraging median overall survival of 21 months was obtained in this non-selected patient population. Conclusion: Using previously identified immunogenic GBM antigens, we provide insights into optimization of vaccines generating effector T cells for glioma patients.Support: Gateway for cancer research, Rising Tide Foundation, Fondation Lionel Perrier, Association Frederic Fellay, Fondation Privée des Hôpitaux Universitaires de Genève, OncoSuisse (to PYD, KFS 3270-08-2013), Fond'action, Association Marietta